A study on foreign market entry strategies towards reducing risk: standardization versus modification / Siti Alyani Isa and Ili Dhaniah Mohd Kamal - Isa, Siti Alyani; Mohd Kamal, Ili Dhaniah (2014)
In this research of International Business, company that produce product for foreign country need to use marketing concept either standardization or modification strategy. This study is useful to international marketing manager to produce new product in foreign country. Company that goes international will selecting a standardization strategy to simplify its internationalization, as it will use the exact same product or service all over its foreign markets as well as in its domestic markets. While for adaptation strategy, it refer to the change of company operates while going on new international markets. It can be drove by different factors as infrastructure of the host country, but companies mainly use an adaptation approach in order to sell their product to a population that have different cultural style. The adaptation strategy enable the company to get higher revenue by convincing more customer who usually have different need and wants from the company's home market's consumers. This strategy involve high cost to be use compare to standardization and usually small company that will using this approach to market their products. This research show the element that influence the degree of standardization. The dependent variable is the degree of standardization and the independent variable are the competition, international experience and cultural differences. We will find the relationship between each elements which being the risk in doing business abroad. The purpose of this research is to investigate the risk of competition, cultural differences and international experience to support the degree of standardization. This research using the quantitative research. Data will be collected by the respondent from company which producing product to foreign country. The data collected using questionnaire and will be distribute to Honda Company at Alor Gajah. We will measure the degree of standardization use by Honda to enter to foreign markets.